CONTRIBUTION OF INDONESIAN ULAMA COUNCIL FOR THE APPLICATION OF ISLAMIC LAW IN INDONESIA - Basyari, Fathurrohman M (Journal of Islamicate Studies, 2019)
This article discusses the contribution of the Indonesian Ulama Council (MUI) to the application of Islamic Law in Indonesia. By using a literature study, this article succeeded in revealing that the position of the MUI was a forum which brought together Indonesian Muslim scholars and scholars and aimed to unite the movements and steps of Muslims in realizing the implementation of Islamic Law in Indonesia. Through religious guidance in the life of the nation and state, the MUI has issued various fatwas. Although it is non-binding, the fatwa of the MUI is one of the sources in the formation of Positive Law in Indonesia. Thus, the presence of the MUI will be increasingly needed in the process of building an Indonesian country whose population is mostly Muslim.